Slice accelerated diffusion-weighted imaging at ultra-high field strength. - Eichner, C; Setsompop, K; Koopmans, P; Lützkendorf, R; Norris, D; Turner, R; Wald, L; Heidemann, R (2014)
PURPOSE: Diffusion magnetic resonance imaging (dMRI) data with very high isotropic resolution can be obtained at 7T. However, for extensive brain coverage, a large number of slices is required, resulting in long acquisition times (TAs). Recording multiple slices simultaneously (SMS) promises to reduce the TA. METHODS: A combination of zoomed and parallel imaging is used to achieve high isotropic resolution dMRI data with a low level of distortions at 7T. The blipped-CAIPI (controlled aliasing in parallel imaging) approach is used to acquire several slices simultaneously. Due to their high radiofrequency (RF) power deposition and ensuing specific absorption rate (SAR) constraints, the commonly used multiband (MB) RF pulses for SMS imaging are inefficient at 7T and entail long repetition times, counteracting the usefulness of SMS acquisitions. To address this issue, low SAR multislice Power Independent of Number of Slices RF pulses are employed. RESULTS: In vivo dMRI results with and without SMS acceleration are presented at different isotropic spatial resolutions at ultra high field strength. The datasets are recorded at a high angular resolution to detect fiber crossings. CONCLUSION: From the results and compared with earlier studies at these resolutions, it can be seen that scan time is significantly reduced, while image quality is preserved.